Obstetric analgesia and anaesthesia in women with inherited bleeding disorders - Chi, Claudia; Lee, Christine A.; England, Adrian; Hingorani, Jaishree; Paintsil, James; Kadir, Rezan A (Thrombosis and Haemostasis, 2009)
A retrospective review was carried out on the methods of obstetric analgesia/anesthesia used in 80 pregnancies amongst 63 women with inherited bleeding disorders (19 factor XI deficiency, 16 carriers of haemophilia, 15 von Willebrand disease, seven platelet function disorders, four factor VII deficiency, one factor VII and XI deficiency and one factor X deficiency). In 72 pregnancies, the woman was seen antenatally in a multidisciplinary clinic to discuss and plan pain relief options. Regional block was performed for 41 pregnancies. The mothers were known to have a bleeding disorder in 35 of these pregnancies. Prophylactic cover was given in 10 pregnancies prior to the insertion of regional block but not required in the remaining 25 pregnancies because the coagulation defects had spontaneously normalised at term. There were six reported adverse effects from regional block similar to that found in the general population: inadequate anesthesia/analgesia (2), bloody tap (2), hypotension and a possible dural puncture which was treated conservatively. There were no reports of long-term complications. The findings show that it is possible to offer women with inherited bleeding disorders the option of regional block provided their coagulation defects have normalised, either spontaneously during pregnancy or following adequate haemostatic cover.
Keywords: Inherited coagulation disorders; regional analgesia; labour pain relief